Influence of combined neuroprotective therapy on obstetrical results of birth in fetes with early form of fetal growth restriction - Puchkov, V. A.; Deinichenko, O. V.; Bohomolova, O. A.; Пучков, Володимир Анатолійович; Дейніченко, Олена Валеріївна; Богомолова, Оксана Андріївна (My University, 2024)
Aim. To evaluate the effectiveness and impact of complex neuroprotective therapy in fetuses with fetal growth retardation on the obstetric outcomes of delivery.